Effect of social cognitive mindfulness on preschool teachers’ professional identity: the mediating role of resilience - Tang, Yanmei; Wang, Ziyue; Yuan, Zongjin (Frontiers in Psychology, 2025)
The current study investigates the effect of social cognitive mindfulness (SCM) on professional identity and the potential mediating role of resilience in this relationship. The professional identity of preschool teachers is assessed both explicitly using a self-reported scale and implicitly using the Implicit Association Test [SC-IAT]. A total of 106 Chinese preschool teachers were randomly recruited from Jiangsu Province. Participants completed the SC-IAT and several questionnaires. Results show that SCM significantly improved the preschool teachers’ professional identity, both implicitly and explicitly. Results also reveal that resilience plays a mediating role in the relationship between SCM and professional identity. Thus, policymakers should focus on the promising impacts of mindfulness to enhance preschool teachers’ professional identities, beliefs, self-concepts, and positive perceptions or emotions in ECE environments, while also incorporating psychological resilience resources.